2019
DOI: 10.2147/cmar.s166638
|View full text |Cite
|
Sign up to set email alerts
|

<p>Statin and metformin therapy in prostate cancer patients with hyperlipidemia who underwent radiotherapy: a population-based cohort study</p>

Abstract: PurposeTo evaluate the association between the use of statins and/or metformin and patient survival in prostate cancer patients in Taiwan.Subjects and methodsNewly diagnosed prostate cancer patients who had hyperlipidemia and received radiotherapy were identified from the National Health Insurance Research Database 2000–2010. The survival rate was estimated by the Kaplan–Meier method. Univariate and multivariate Cox regression analyses were performed to examine the association of mortality. Sensitivity analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Moreover, a phase II trial observed prostate-specific antigen (PSA) secretion was decreased by the use of a high-dose metformin in progressive metastatic CRPC (9). Recently, a population-based cohort study showed encouraging results that metformin use after diagnosis of PCa might increase survival of patients (10). All of these suggest that metformin could be a useful medication for PCa therapy, but more studies are still needed to further evaluate such a notion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a phase II trial observed prostate-specific antigen (PSA) secretion was decreased by the use of a high-dose metformin in progressive metastatic CRPC (9). Recently, a population-based cohort study showed encouraging results that metformin use after diagnosis of PCa might increase survival of patients (10). All of these suggest that metformin could be a useful medication for PCa therapy, but more studies are still needed to further evaluate such a notion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies that were not relevant to assessing the effects of statin use among PCa patients or had no extractable outcome data, as well as commentaries, conference abstracts, editorials, and reviews, were excluded. Finally, 12 studies met the inclusion criteria for the current meta-analysis [8,9,[23][24][25][26][27][28][29][30][31][32]. Six studies investigated the effects of statin use in PCa patients using ADT as their primary treatment [23][24][25][26][27][28].…”
Section: Literature Searchmentioning
confidence: 99%
“…Six studies investigated the effects of statin use in PCa patients using ADT as their primary treatment [23][24][25][26][27][28]. The other six studies investigated the effects of statin use in PCa patients using definitive therapy as their primary treatment [8,9,[29][30][31][32].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations